ОСНОВНІ ПРИНЦИПИ ОРГАНІЗАЦІЇ ЕЛЕКТРОННИХ ЗАСОБІВ НАВЧАННЯ МАЙБУТНІХ ДИСПЕТЧЕРІВ ІЗ ЗАБЕЗПЕЧЕННЯ ПОЛЬОТІВ - Грам, Ольга (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Розглянута проблема вдосконалення засобів навчання майбутніх диспетчерів із забезпечення польотів. З’ясована необхідність створення і впровадження електронних засобів навчання даних фахівців на основі вимог до розробки подібних засобів та з урахуванням принципів організації педагогічних програмних засобів. На основі розглянутих наукових досліджень і публікацій та законодавчих актів розроблено та обґрунтовано основні принципи організації електронних засобів навчання майбутніх диспетчерів із забезпечення польотів. Рассмотрена проблема совершенствования средств обучения будущих диспетчеров по обеспечению полетов. Выяснена необходимость создания и внедрения электронных средств обучения данных специалистов на основе требований к разработке подобных средств и с учетом принципов организации педагогических программных средств. На основе рассмотренных научных исследований и публикаций и законодательных актов разработаны и обоснованы основные принципы организации электронных средств обучения будущих диспетчеров по обеспечению полетов. The problem of improvement of educational aids of future flight dispatchers was reviewed. Clarified the need for the creation and implementation of electronic educational aids of such specialists leading to the design requirements for such facilities and taking into account the principles of educational software. On the basis of the research and publications and legislation developed and proved the basic principles of electronic educational aids of future flight dispatchers. Compliance with all principles of educational software will help to develop an aid that can interact with other information systems; it will match the content of both international and national standards; is easy to use and accessible to mastering man who has only general computer skills; data structure will ensure cataloging and search for objects by their properties; ensure the protection of intellectual property developer and customer of electronic educational aids.